Formulation and Evaluation of Herbal Antioxidant Cream from Papaya Latex and Banana Peel Extract (Asian Journal of Pharmaceutics (AJP), 2025)
There is a growing interest in developing natural skincare products with potent antioxidantproperties to combat oxidative stress and premature aging. Objective: To formulate and evaluate an herbalantioxidant cream using papaya latex (Carica papaya) and banana peel extract (Musa spp.). Methods: Extractionof bioactive compounds from papaya latex and banana peel was performed, followed by antioxidant testing andcream formulation. The cream was evaluated for pH, viscosity, spreadability, phase separation, sensory qualities,and in vitro antioxidant activity. Results: Papaya latex exhibited greater antioxidant activity than banana peelextract. Creams demonstrated desirable physicochemical properties and increased antioxidant efficacy withhigher extract concentrations. Conclusion: The herbal cream showed effective antioxidant potential, stability,and skin compatibility, offering a promising natural skincare alternative.